Estudo químico e atividades farmacológicas em esponjas de água doce da Amazônia - (:unkn) unknown (Universidade Federal do Amazonas, 2020)
Sponges (phylum Porifera), are aquatic animals, with marine and freshwater specimens. Although found in several regions, freshwater sponges are one of the least known faunas in the world. Most studies are reported with marine sponges. Sponges have an enormous biotechnological potential in the search for natural products due to the various biological activities. Just like marine sponges, which feature various bioactive compounds (eg, alkaloids, macrolides, peptides, polyketides, quinines, sterols and terpenoids), species of freshwater sponges are reported to be chemically made up of fatty acids and sterols. In the chemical study of freshwater sponges, sterols deserve attention due to the great diversity they present and the great biological potential. The compounds produced by sponges are important natural resources, which can lead to the production of drugs to help mainly in the treatment of neurodegenerative diseases and malaria. Due to the absence of chemical and biological studies of these organisms in the Amazon, it was the reason for carrying out work in the region due to their great occurrence. The present work aimed to characterize and identify chemical compounds from the metabolism of sponges by means of metabolomic analysis and to evaluate the inhibition of acetylcholinesterase and butyrylcholinesterase (AChE and BuChE) and the inhibition of Plasmodium falciparum, of methanol extracts from sponges of freshwater from the Amazon (Drulia uruguayensis, Drulia cristata, Drulia browni and Metania reticulata). To verify the chemical profile of the extracts, analyzes were performed in mass spectrometry by direct insertion and high- performance liquid chromatography coupled to a high-resolution mass spectrometry detector. To verify the inhibitory activity of acetylcholinesterase, the Ellman method was used, modified by Lima, and the inhibitory activity of P. falciparum was used according to the FIOCRUZ-AM platform. All extracts inhibited AChE, however, no activity was observed in relation to BChE. The extract of Drulia uruguayensis showed greater inhibition of AChE, with IC50 = 1.04 mg/mL. For antiplasmodial activity, all species showed inhibition of P. falciparum, but the sample of Metania reticulata was the most efficient with IC50 = 2.7 μg/mL. The metabolomic analysis carried out by mass spectrometry showed the presence of biomarkers that helped differentiate species, the biomarkers found in the active extracts were identified as fatty acids and sterols. The metabolites of freshwater sponges have few studies in the literature, however with the results obtained, it has helped in the enrichment and significance of studies with freshwater sponges, which already prove that in the Amazon region sponges have metabolites with similar activities to marine sponge.
Keywords: Animais de água doce - Amazônia; Produtos naturais - Amazônia; CIENCIAS DA SAUDE: FARMACIA; CIENCIAS EXATAS E DA TERRA: QUIMICA: QUIMICA ORGANICA: QUIMICA DOS PRODUTOS NATURAIS; Esponja; Bioatividade; Esteróis; Metaboloma; Amazônia